The Impact of Accounting Earnings Disclosures on Stock Prices in Malaysia: An Emerging Market - Cheng, Fan Fah (2000)
This study aims to evaluate the usefulness of accounting earnings disclosures as determinants of share price changes both in sign and magnitude for an emerging market. This thesis attempts to answer the contentious question as to whether the accepted findings in several institutionally more developed capital markets about the value relevance of accounting earnings is applicable to firms traded in more speculative emerging markets. Many studies have identified the different characteristic of these two types of markets. Amongst the more important distinguishing characteristics of emerging and developed capital markets are (a) economic and institutional differences, (b) size-related features, (c) liquidity differences, (d) information availability and (e) the nature of the market's integration within the financial system. The returns-to-earnings relation is based on three postulated links. These are links between the (1) present price and the future dividends, (2) future dividends and the future earnings, and (3) future earnings and the current earnings. These links have been evidenced in many empirical findings reported by researchers on share price valuation, on earnings and dividends relation, on random walk theory of earnings, and many others studies. A pioneer study on the directional sign effect of unexpected earnings on stock returns appeared in 1968, the magnitude effect was first studied in 1979.